(untitled) (Research, Society and Development, 2021)
This study aims to discuss, based on findings in the literature, the difficulties encountered in health care for people with deafness. It is a descriptive study, of the type integrative literature review, of a qualitative character, the search occurred in the databases: LILACS, SCIELO and BDENF, via VHL, and Scholar Google. The articles were collected in the period of January 2021. The descriptors: Health care, Deafness and public health were used, located in the list of Health Sciences Descriptors (DECs). After applying the eligibility criteria, 14 studies remained. The main difficulty in assisting the deaf is the communication barrier, due to the lack of knowledge of the health professional about the Brazilian sign language. In addition, the absence of a professional interpreter in the institutions, discrimination, stereotypes. It is concluded that it is necessary to have trained professionals to attend deaf patients in order to guarantee humanitarian assistance, comprehensive and free from prejudice.